What works for wellbeing? A systematic review of wellbeing outcomes for music and singing in adults. (January 2018) - Daykin, Norma; Mansfield, Louise; Meads, Catherine; Julier, Guy; Tomlinson, Alan; Payne, Annette; Grigsby Duffy, Lily; Lane, Jack; D'Innocenzo, Giorgia; Burnett, Adele; Kay, Tess; Dolan, Paul; et al.
Aims: The role of arts and music in supporting subjective wellbeing (SWB) is increasingly recognised. Robust evidence is needed to support policy and practice. This article reports on the first of four reviews of Culture, Sport and Wellbeing (CSW) commissioned by the Economic and Social Research Council (ESRC)-funded What Works Centre for Wellbeing (https://whatworkswellbeing.org/ ). Objective: To identify SWB outcomes for music and singing in adults. Methods: Comprehensive literature searches were conducted in PsychInfo, Medline, ERIC, Arts and Humanities, Social Science and Science Citation Indexes, Scopus, PILOTS and CINAHL databases. From 5, 397 records identified, 61 relevant records were assessed using GRADE and CERQual schema. Results: A wide range of wellbeing measures was used, with no consistency in how SWB was measured across the studies. A wide range of activities was reported, most commonly music listening and regular group singing. Music has been associated with reduced anxiety in young adults, enhanced mood and purpose in adults and mental wellbeing, quality of life, self-awareness and coping in people with diagnosed health conditions. Music and singing have been shown to be effective in enhancing morale and reducing risk of depression in older people. Few studies address SWB in people with dementia. While there are a few studies of music with marginalised communities, participants in community choirs tend to be female, white and relatively well educated. Research challenges include recruiting participants with baseline wellbeing scores that are low enough to record any significant or noteworthy change following a music or singing intervention. Conclusions: There is reliable evidence for positive effects of music and singing on wellbeing in adults. There remains a need for research with sub-groups who are at greater risk of lower levels of wellbeing, and on the processes by which wellbeing outcomes are, or are not, achieved.